Morphological method for the diagnosis of human adult type hypolactasia. Issue 8 (August 1994) - Maiuri, L; Rossi, M; Raia, V; Paparo, F; Coletta, S; Mazzeo, F; Breglia, A; Auricchio, S
Abstract : The primary adult type hypolactasia is the most common form of genetically determined disaccharidase deficiency. This study examined a large and homogeneous population of the south of Italy: surgical biopsy specimens of proximal jejunum from 178 adult subjects have been assayed for disaccharidase activities; the expression of lactase protein and lactase activity has also been investigated on tissue sections by immunomorphological and enzymohistochemical techniques. Histograms of lactase to sucrase ratio were found to provide a useful distribution of the lactase activity; a lactase to sucrase ratio of 0.17 was found to show discrimination between tissues with persistence of high lactase activity and tissues with adult type hypolactasia. In all 28 subjects with persistent high lactase activity, a uniform distribution of lactase protein and lactase activity in all villus enterocytes was detected, whereas in all 150 subjects with adult type hypolactasia a variable number of villus enterocytes failed to express the lactase. Moreover in hypolactasic samples the lactase activity on tissue sections was constantly detected later than in samples with persistent high lactase activity. The absolute correlation between the immunohistochemical and enzymohistochemical features and the assessment of lactase activity in intestinal homogenates suggests that the morphological criteria are an alternative method for the diagnosis of adult type hypolactasia in human biopsy specimens from proximal small jejunum.